Dots, lines, contours, and ends: An image-based review of esophageal pathology. (2021) - Keshav, Nandan; Khalid, Sameen; Parasher, Gulshan; Cassidy, Fiona; Thompson, William; Shiehmorteza, Masoud
Highlights: Learning Point #1 : Small ulcers on esophagography are usually attributable to herpes esophagitis and drug-induced esophagitis. Although rare, Crohn's disease may produce small apthoid ulcers. Large ulcers are usually attributable to CMV or HIV esophagitis. Learning Point #2 : The early findings of candida are plaques that mimic glycogenic acanthosis. When plaques are seen, consider early candida or glycogenic acanthosis. When shaggy esophagus is identified, consider candidiasis. Learning Point #3 : Varices and varicoid esophageal carcinoma may appear similar on imaging. The presence of obstruction and lack of change with time and position should sway the Radiologist to diagnosing varicoid esophageal carcinoma. Learning Point #4 : Transverse esophageal lines should suggest the entities of feline esophagus and idiopathic eosinophilic esophagitis. Learning Point #5 : Esophageal contour abnormalities may suggest extrinsic or intrinsic lesions. Extrinsic lesions include aberrant vessels. Intrinsic lesions include intramural pseudodiverticulosis, gastroesophageal reflux, Barrett's esophagus, and esophageal cancer. Abstract: Esophageal pathologies encountered on fluoroscopic examination may pose a diagnostic challenge to the interpreting Radiologist. Understanding the varied imaging appearances of esophageal pathology requires a thorough understanding of barium esophagography. This article reviews the various fluoroscopic imaging findings of different esophageal pathologies by describing an approach to image interpretation centered on dots, lines, contours, and ends. By utilizing this approach, the Radiologist will be better positioned to reconcile seemingly disparate pathologies into a cogent and succinct differential diagnosis.